Practical Suggestions for Win-Win, Win-Lose, Lose-Win, and Lose-Lose Strategies in Mediation or Arbitration - Donald, L. Buresh (Journal of Human Psychology, 2022)
This essay discusses the practical aspects of mediation and arbitration. The article outlines effective steps to implement win-win, win-lose, lose-win, and lose-lose negotiation strategies. It is posited that with a win-win strategy, the job of a mediator or arbitrator is to find a win-win scenario that is acceptable to both sides. The role of a mediator or arbitrator when the parties are engaging in win-lose, lose-win, and lose-lose strategies is different in that at least one of the parties is not seeking a win for all sides. In particular, when the parties are not involved in a win-win, and court is an option, the parties need to gain as much information about the opposing party as possible to use it to their advantage in court. This is unfortunate but, at times, a necessary result of not participating in a win-win outcome.
Keywords: Win-Win Strategy; Win-Lose Strategy; Lose-Win Strategy; Lose-Lose Strategy; Mediation; Arbitration